Does end-of-life care differ for Anglophones and Francophones? A retrospective cohort study of decedents in Ontario, Canada - Guerin, Ewa; Batista, Ricardo; Hsu, Amy. T.; Gratton, Valérie; Chalifoux, Mathieu; Prud’homme, Denis; Tanuseputro, Peter (Journal of Palliative Medicine, 2018)
Background: Approximately half of decedents in Ontario, Canada, receive some palliative care, but little is known about the influence of language on the nature of these services. Objective: To examine differences between English- and French-speaking residents of Ontario in end-of-life care and outcomes (e.g., health care costs and location of death). Design: A retrospective cohort study using multiple linked databases. Setting/Subjects: A population-based cohort of decedents in Ontario (2010–2013) who were living in long-term care institutions (i.e., nursing homes) or receiving home care before death (N = 25,759). Data from two regions with higher representations of Francophones were examined, with the final distribution by primary language being 75% Anglophone, 18% Francophone, and 7% other languages. Results: Compared with Anglophones, Francophones were more frequent users of long-term care (47.6% vs. 37.1%) and less frequent users of home care (71.3% vs. 76.3%). In adjusted models, the number of days spent in hospital in the last 90 days of life was similar between Anglophones and Francophones, although the odds of dying in hospital were significantly higher among the latter. The mean total health care cost in the last year of life was slightly lower among French ($62,085) compared with English ($63,814) speakers. Conclusions: There are statistically significant differences in end-of-life outcomes between linguistic groups in Ontario, namely more institutionalization in long-term care, less home care use and more deaths in-hospital among Francophones (adjusted). Future research is needed to examine the cause of these differences. Strategies to ensure equitable access to quality end-of-life care are required.

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les trajectoires d'aînés dans le contexte de l'accès à des services sociaux et de santé en français dans la région d'Ottawa - Kubina, Lucy-Ann; Savard, Jacinthe; Drolet, Marie; Savard, Sébastien; Benoît, Josée (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2018)

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.